2024
DOI: 10.1021/acsami.4c01071
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Transparent, and Bifacial Perovskite Solar Cells and Modules Using the Wide-Band Gap FAPbBr3 Perovskite Absorber

Farshad Jafarzadeh,
Luigi Angelo Castriotta,
Marie Legrand
et al.

Abstract: Perovskite solar cells (PSCs) offer impressive performance and flexibility, thanks to their simple, low-temperature deposition methods. Their band gap tunability allows for a wide range of applications, transitioning from opaque to transparent devices. This study introduces the first flexible, bifacial PSCs using the FAPbBr 3 perovskite. We investigated the impact of optimizing electron and hole transport layers on the cells' bifaciality, transparency, and stability. PSCs achieved a maximum power conversion ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(116 reference statements)
0
0
0
Order By: Relevance
“…Although FAPbBr 3 is scarcely used as a photovoltaic absorber material due to its large bandgap (∼2.3 eV), , this composition was selected to study the details of the relaxation phenomena in perovskites for several reasons. First, several studies have shown that, unlike its iodide-based alternative, FAPbBr 3 directly forms the cubic perovskite phase without transient or permanent inclusion of intermediate complexes or secondary phases. , Second, light-induced halide segregation is avoided, as FAPbBr 3 is a single halide composition. , Lastly, compared with MA-based perovskite compositions, FAPbBr 3 is relatively stable in air and under illumination .…”
mentioning
confidence: 99%
“…Although FAPbBr 3 is scarcely used as a photovoltaic absorber material due to its large bandgap (∼2.3 eV), , this composition was selected to study the details of the relaxation phenomena in perovskites for several reasons. First, several studies have shown that, unlike its iodide-based alternative, FAPbBr 3 directly forms the cubic perovskite phase without transient or permanent inclusion of intermediate complexes or secondary phases. , Second, light-induced halide segregation is avoided, as FAPbBr 3 is a single halide composition. , Lastly, compared with MA-based perovskite compositions, FAPbBr 3 is relatively stable in air and under illumination .…”
mentioning
confidence: 99%